Visual Feedback and Virtual Reality in Gait Rehabilitation of Hemiparetic Children and Teenagers after Acquired Brain Injury: A Pilot Study - Daniele Panzeri; Chiara Genova; Geraldina Poggi; Sandra Strazzer; Emilia Biffi (MDPI AG, 2022)
Hemiparesis as a term refers to a neurological disorder that can be extremely variable, especially with regard to walking abilities. Few works have assessed the use of virtual reality and biofeedback in children and adolescents with hemiparesis. The aim of this study is to provide insights about the rehabilitation of hemiparetic children and teenagers with visual biofeedback in a virtual reality environment. Six hemiparetic subjects (mean age 13.13 years, age range (7-18), 4 males) received 20 personalized rehabilitation GRAIL (Gait Real-time Analysis Interactive Lab) sessions plus 20 sessions of traditional physiotherapy. After an initial evaluation of rehabilitation needs, training focused on gait pattern correction (GP), walking endurance (WE), or gross motor functions (GMFs). All subjects were assessed for their gait analysis by GRAIL, the Gross Motor Function Measure (GMFM), and the 6-Minute Walking Test (6MWT) before and after rehabilitation. All subjects reached their rehabilitation goals, save for one who showed reduced collaboration. In addition, 4 subjects reached a better GP, 3 subjects reported improvements in WE, and 2 subjects improved in GMF. This personalized training with visual biofeedback delivered in a VR setting appears to be effective in modifying motor control and improving gait pattern, in addition to resistance and functional activities, in subjects with hemiparesis.